Circular Economy of Used Cooking Oil in Indonesia: Current Practices and Development in Special Region of Yogyakarta - B. Endo Gauh Perdana (Journal of World Trade Studies, 2021)
Used Cooking Oil (UCO) has become an inherent lifestyle of Indonesian people as frying is the main cooking method. As UCO ways of disposal have not been properly managed, the question on how UCO should be managed contributes to the adaptability of circular economy strategies moving away from throw-away culture. This study adopts desk research methods collecting relevant information from articles, journals, and books. Utilizing six dimensions – governmental, economic, environmental, technological, societal, and behavioural – of CE research for built-in environment and its conceptual limitations, this study finds that the absence of UCO governance networks contributes to the establishment of UCO collection initiatives from private sectors and community-based programs. The adoption of CE in terms of its definition and conceptual frameworks are accentuated with varying levels of emphasis on waste separation and collection systems. This study also argues that the dimensions of CE and its limitations in terms of governance and management, and social and cultural definitions are strictly attributed to incentivized UCO collection models while business sectors tend to foster limited energy recovery of UCO.